VH

GIẢI phương trình A=√(6-x) +√(x+2) =x^2 -6x+13

HN
14 tháng 10 2016 lúc 18:18

Xét vế trái , áp dụng bđt Bunhiacopxki : \(\left(1.\sqrt{6-x}+1.\sqrt{x+2}\right)^2\le\left(1^2+1^2\right).\left(6-x+x+2\right)\)

\(\Rightarrow\sqrt{6-x}+\sqrt{x+2}\le4\)

Xét vế phải : \(x^2-6x+13=\left(x^2-6x+9\right)+4=\left(x-3\right)^2+4\ge4\)

Vậy PT tương đương với \(\hept{\begin{cases}\sqrt{6-x}+\sqrt{x+2}=4\\x^2-6x+13=4\end{cases}}\) \(\Leftrightarrow\hept{\begin{cases}x=2\\x=3\end{cases}}\)(loại vì không thỏa mãn)

Vậy Pt vô nghiệm.

Bình luận (0)